ANALISIS KESALAHAN PEMECAHAN MASALAH MATEMATIS SISWA DALAM MENYELESAIAKAN SOAL OPERASI HITUNG CAMPURAN BILANGAN CACAH DAN PECAHAN - Vindi Fujia Syavira; Chandra Novtiar (IKIP Siliwangi, 2021)
This research aims to analyze students' errors in terms of mathematical problem-solving skills when solving the operation of calculating a mixture of numbers and fractions. The subjects who have been studied are students of the 8th grade of PGRI 4 Cimahi Junior High School in the academic year 2019-2020. This research is conducted with descriptive methods that aim to obtain an overview of student errors in solving problems solving the problem of calculating the number of numbers and pacahan, then the data collection technique used is to use the documentation of the instrument of the problem as many as 6 questions of description that have been done by students. Once the data is obtained, the researcher analyzes it with qualitative descriptive analysis. The results obtained from this study, stated that students' errors in working on problem solving problems are relatively high and get an overall average percentage of 70.45%. This shows that students can work on the problem with the right answer, but many skip the steps of problem solving.